FRI0574 Radiofrequency echographic multi spectrometry (REMS) for the non-ionising diagnosis of osteoporosis at femoral neck: results of a multicenter clinical study comparing rems and dxa. (12th June 2018) - Cavalli, L.; Arioli, G.; Bianchi, G.; Caffarelli, C.; Matucci Cerinic, M.; Cianferotti, L.; Conversano, F.; Di Paola, M.; Gatti, D.; Girasole, G.; Giusti, A.; Gonnelli, S.; et al.
Abstract : Background: Radiofrequency Echographic Multi Spectrometry (REMS) is an innovative densitometric technique able to automatically provide BMD values, which it has been shown to highly correlate with BMD obtained by DXA. 1 Objectives: To evaluate the accuracy of REMS measurements in postmenopausal women's femoral neck health assessment versus DXA results in a multicenter clinical study. Methods: In seven Italian referral centres for osteoporosis management, 1659 postmenopausal women (51–70 years old) were enrolled. Both DXA and REMS examinations were performed on each patient at femoral neck, in the strictest adherence to the corresponding guidelines. After excluding the scans affecting by errors, the REMS diagnostic accuracy was evaluated by assessing sensibility and specificity in the discrimination between "osteoporotic" and "healthy" patients; the degree of correlation between DXA-BMD and REMS-BMD was quantified through Pearson's correlation coefficient (r) evaluation. In addition, the agreement between DXA-BMD and REMS-BMD was measured calculating the root mean square error ( RMSE ). Results: A strong correlation (r=0.94, p<0.001) was detected between BMD obtained by DXA and REMS – estimated BMD at femoral neck, with a low residual error ( RMSE =0.034 g/cm 2 ). In addition to this, REMS resulted to have a high capability to discriminate osteoporotic from healthy patients (sensibility=94.4%, specificity=95.6%). Conclusions: Thanks to its high capability to identify osteoporotic patients, and the strong correlation with DXA parameters, REMS has been shown to be an accurate non-ionising approach to detect osteoporosis at femoral neck. Reference: [1] Casciaro S, et al. UMB2016;42:1337–56. Disclosure of Interest: None declared